REFLECTION OF KAIZEN AS THE PHILOSOPHY OF THE JAPANESE NATION’S LIFE IN RIKUOU DRAMA - Amalia, Aan (CENTRAL ASIA AND THE CAUCASUS, 2022)
Japan is one of the most developed countries in Asia. Japanese people are also famous for their work ethic. In addition, Japanese people also have the characteristics of discipline, persistence, loyalty and hard work. With such characteristics, Japan has become a very developed country, and can be in line with other developed countries such as America and other European countries.This paper also reviews the Japanese philosophy of life, one of which is the philosophy of kaizen. A philosophy that emphasizes continuous improvement and refinement is also carried out simply and gradually, until it finally reaches perfection.In the Rikuou drama, the writer finds many kaizen philosophies that are highlighted and displayed in every scene of the episode, so the writer feels interested in putting it in the form of this scientific article.